Immune deficiency, autoimmune disease and intellectual disability: A pleiotropic disorder caused by biallelic variants in the TPP2 gene. Issue 6 (21st February 2021) - Atallah, Isis; Quinodoz, Mathieu; Campos‐Xavier, Belinda; Peter, Virginie G.; Fouriki, Athina; Bonvin, Christophe; Bottani, Armand; Kumps, Camille; Angelini, Federica; Bellutti Enders, Felicitas; Christen‐Zaech, Stéphanie; Rizzi, Mattia; et al.
Abstract: Four individuals from two families presented with a multisystemic condition of suspected genetic origin that was diagnosed only after genome analysis. The main phenotypic features were immune system dysregulation (severe immunodeficiency with autoimmunity) and intellectual disability. The four individuals were found to be homozygous for a 4.4 Kb deletion removing exons 20–23 (NM_003291.4) of the TPP2 gene, predicting a frameshift with premature termination of the protein. The deletion was located on a shared chromosome 13 haplotype indicating a Swiss founder mutation. Tripeptidyl peptidase 2 (TPP2) is a protease involved in HLA/antigen complex processing and amino acid homeostasis. Biallelic variants in TPP2 have been described in 10 individuals with variable features including immune deficiency, autoimmune cytopenias, and intellectual disability or chronic sterile brain inflammation mimicking multiple sclerosis. Our observations further delineate this severe condition not yet included in the OMIM catalog. Timely recognition of TPP2 deficiency is crucial since (1) immune surveillance is needed and hematopoietic stem cell transplantation may be necessary, and (2) for provision of genetic counselling. Additionally, enzyme replacement therapy, as already established for TPP1 deficiency, might be an option in the future. Abstract :